2016
DOI: 10.1111/clr.12853
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital impressions of multiple dental implants: an in vitro study

Abstract: Based on the findings of this in vitro study, the 3M True Definition and Trios scanner demonstrated the highest accuracy. The Lava COS was found not suitable for taking implant impressions for a cross-arch bridge in the edentulous jaw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
172
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(209 citation statements)
references
References 34 publications
9
172
1
3
Order By: Relevance
“…A study with a six‐implant edentulous mandibular scenario reported that the TRIOS and True Definition scanner were more accurate than Omnicam, but there was no conventional control group (Vandeweghe et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with a six‐implant edentulous mandibular scenario reported that the TRIOS and True Definition scanner were more accurate than Omnicam, but there was no conventional control group (Vandeweghe et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study with a six‐implant edentulous mandibular scenario reported that the TRIOS and True Definition scanners were more accurate than Omnicam, but there was no conventional control group (Vandeweghe et al. ). An in vitro study with a six‐implant edentulous maxilla scenario and True Definition scanner reported that it provides clinically acceptable results, but there was no conventional control group as well (Gimenez‐Gonzalez et al.…”
mentioning
confidence: 99%
“…Using the program N Query Advisor 4.0 with a level of significance of 0.05 and four study groups, based on the article of Vandeweghe S et al [26] and a power of 80%, we obtained a value of six participants per group ( n = 6). Given that there was the possibility that the standard deviation of our work was a little wider, we decided to raise the number the number of participants to n = 10; As it is an in vitro study, there were no patients exposed to unnecessary risks, and it could be safely increased from 6 to 10, in order to improve the reliability and precision of the results.…”
Section: Methodsmentioning
confidence: 99%
“…Because the scanbody is in the form of a straight rod, soft tissue may collapse during and after fastening the scanbody in the oral cavity; this may result in changes in the soft‐tissue profile . In addition, incorrect fastening of the scanbody might reduce the accuracy of the prosthesis . Moreover, it is cumbersome to perform 2 scans: one without connecting the scanbody, required to obtain the soft‐tissue profile of the implant; and one after the scanbody is connected, required to record the position of the implant.…”
mentioning
confidence: 99%